Leading the Modern University : York University's Presidents on Continuity and Change, 1974-2014 - Marsden, Lorna R. (Book collections on Project MUSE., 2016)
"Founded in 1959, York University is now the second largest university in Ontario and third largest university in Canada. However, starting in the 1970s the success of the university was far from guaranteed. Leading the Modern University documents the challenges and solutions that five successive university presidents (H. Ian Macdonald, Harry Arthurs, Susan Mann, Lorna Marsden, and Mamdouh Shoukri) encountered from the very early 1970s up to 2014. This book is the rare occurrence where a series of university presidents describe and analyze the challenges they faced regarding financing, morale crises, and succession. With each president contributing a chapter, covering her or his own years in office, Leading the Modern University reveals that large public institutions have internal dynamics and external forces that supersede any individual leader's years in office. This is a case study for those interested in organizational change as seen by the leadership of a major public institution during a dynamic period in higher education."--